Protection of the Safety of Dental Health Workers Against Radiation Exposure Dental X-Ray - Edy Susanto; Endang Larasati; Hardi Warsono; Tri Yuniningsih (Jurnal Kesehatan Gigi, 2021)
ABSTRACTThe use of X-rays is an integral part of clinical dentistry because it can help doctors when diagnosing a clinical symptom experienced by a patient through radiological images (x-rays). Radiation used in radiology is not only useful for helping to establish a diagnosis, it can also pose a danger to radiation workers and the general public who are around the radiation source. The method used is literature review, namely by examining data sources in the form of articles in research journal databases both from within and outside the country through e-journal searches, government regulations, and internet article sources that can be accounted for. The results showed that diagnostic radiology services are an integral part of medical services that need special attention because apart from being useful in establishing a diagnosis, it is also very dangerous for patients, staff and the surrounding environment if it is not carried out properly. In an effort to achieve quality and safe radiology services, excellent management and technical management are needed that are supported by good facilities/infrastructure, human resources and equipment.Dental hygienists should have knowledge of the application of safe radiation practices to all patients requiring radiographic examination. The findings of this study indicate that participants practice safer radiographic techniques with years of experience along with higher levels of education.